Acoustic pressure of a system of concentric annular sources in a parallel-piped layer of a gaseous medium - RDZANEK, Witold (Archives of Acoustics, 1985)
In this paper, an expression was derived for the acoustic pressure distribution in the near and far fields, radiated by a system of planar concentric annular sources. The propagation of the pressure wave was considered for a parallel--piped layer, bounded by rigid baffles, filled with a lossless gaseous medium. It was assumed that the system of sources, with known axially-symmetric vibration velocity distribution, was on one of the planar and rigid baffles. Linear phenomena dependent sinusoidally on time were analysed.By solving the Neumann boundary problem by means of the method of Hankel transforms of the zeroth order, an integral expression was obtained for the acoustic pressure distribution in a parallel-piped layer. The pressure, expressed by an integral in the complex variable plane, was represented in the form of a series of residua at the poles of the subintegral function, giving a formula, convenient for practical calculations and easy to interpret, in the form of a series of normal waves. The theoretical analysis of the acoustic pressure distribution was supported by numerical examples, for which curves of acoustic pressure were plotted as a function of the distance from the source.